2005
DOI: 10.1016/s1808-8694(15)31288-x
|View full text |Cite
|
Sign up to set email alerts
|

Update in Obstructive Sleep Apnea Syndrome in Children

Abstract: The prevalence of OSAS in children is 0.7-3%, with peak incidence in pre-schoolers. It is characterised by partial or complete upper airway obstruction during sleep, causing intermittent hypoxia. Both anatomical (severe nasal obstruction, craniofacial anomalies, hypertrophy of the pharyngeal lymphoid tissue, laryngeal anomalies, etc.) and functional factors (neuromuscular diseases) predispose to OSAS during childhood. The main cause of OSAS in children in adenotonsillar hypertrophy. The most common clinical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 29 publications
0
20
0
8
Order By: Relevance
“…(30) In the present study we chose to use the AHI for the diagnosis and classification of OSAHS in children, since this is the procedure adopted by the authors in their clinical practice and is in accordance with many recently published studies on the theme. (13)(14)(15) We concluded that the symptoms most frequently observed in children and adolescents with OSAHS in this study were snoring and chronic nasal obstruction. In addition, the most severe cases of OSAHS occur in children under six years of age, which coinis six to nine times greater in children with learning problems at school than in the general pediatric population.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…(30) In the present study we chose to use the AHI for the diagnosis and classification of OSAHS in children, since this is the procedure adopted by the authors in their clinical practice and is in accordance with many recently published studies on the theme. (13)(14)(15) We concluded that the symptoms most frequently observed in children and adolescents with OSAHS in this study were snoring and chronic nasal obstruction. In addition, the most severe cases of OSAHS occur in children under six years of age, which coinis six to nine times greater in children with learning problems at school than in the general pediatric population.…”
Section: Resultsmentioning
confidence: 53%
“…(18) This is due, principally, to the fact that such questionnaires depend on the reports of severity of OSAHS, following the parameters for the pediatric age bracket, was normal with an AHI < 1; mild with an AHI between 1 and 5; moderate when the AHI is between 5 and 10 and serious when the AHI is >10. (13)(14)(15) The parents or legal guardians of all children included in the study agreed to participate and gave written informed consent. The statistical analysis was carried out using the Statistical Package for the Social Sciences, version 10.0 (SPSS Inc., Chicago, IL, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory virus genomes were searched in adenoids (AD), palatine tonsils (PT) and nasopharyngeal secretions (NPS) obtained from all 172 children (91 males) aged 1-13 years (mean 5.8 years) who underwent adenotonsillectomy to treat adenotonsillar hypertrophy with clinical evidence of obstructive sleep apnoea syndrome [6] or recurrent adenotonsillitis according to Paradise criteria [18]. Patients were treated at the division of Otorhinolaryngology of the School of Medicine of RibeirĂŁo Preto, University of SĂŁo Paulo, between May 2010 and June 2012.…”
Section: Patients and Samplingmentioning
confidence: 99%
“…The prevalence of such risk factors has increased in the adult population, however, have also been found high prevalence in children and adolescents [3][4][5] . Among children and adolescents, excess body weight is an increasingly common risk factor 6 , causing, besides cardiovascular problems, sleep apnea, hypertension, osteoarticular disorders and low self-esteem [7][8][9][10] . Physical inactivity is another concern since risk factor studies of Brazilian children and adolescents revealed insufficient practice of physical activities 11 .…”
Section: Introductionmentioning
confidence: 99%